Automated highly multiplexed super-resolution imaging of protein nano-architecture in cells and tissues - Klevanski, Maja; Herrmannsdörfer, Frank; Saß, Steffen; Venkataramani, Varun; Heilemann, Mike; Kuner, Thomas (Nature Communications, 2020)
Super-resolution imaging of multiple target proteins in the same sample can provide important information of cellular nanostructure, but has not been routinely achieved. Here, the authors present a fully automated 3D STORM approach using a re-staining protocol to image 15 targets in single cells and 16 targets in neuronal tissue.